2009
DOI: 10.1063/1.3093955
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between structural and magnetic properties of L1-FePt(001) thin films directly grown on MgO(001)

Abstract: We present a detailed study of the magnetic and structural properties of L1 0 -FePt thin films. The films are prepared via molecular beam epitaxy directly onto MgO͑001͒ substrates, i.e., without buffer layer. Despite the large lattice misfit between the in-plane lattice parameters of L1 0 FePt and MgO, highly ordered thin films are obtained with the easy magnetization c axis perpendicular to the film plane. Via high resolution transmission electron microscopy and Rutherford backscattering measurements we focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
2
19
0
2
Order By: Relevance
“…3.2 L10-ordered FePt film structure (020), in agreement with the previous reports 22,23) , and these dislocations are effectively decreasing the lattice misfit of 9 % to be nearly zero percent. A presence of crystallographic defect, A-B in Fig.…”
Section: A D V a N C E P U B L I C A T I O Nsupporting
confidence: 79%
“…3.2 L10-ordered FePt film structure (020), in agreement with the previous reports 22,23) , and these dislocations are effectively decreasing the lattice misfit of 9 % to be nearly zero percent. A presence of crystallographic defect, A-B in Fig.…”
Section: A D V a N C E P U B L I C A T I O Nsupporting
confidence: 79%
“…To avoid island growth 16 and guarantee a flat film surface, however, the FePt films for this study are directly grown on MgO under well-tested conditions. 17 Unfortunately it is not possible to prepare a film with the magnetic main axis, which is along the c lattice direction, purely parallel to the film surface (a variant) on MgO(001) at low enough temperatures to avoid dilution of the isotopic multilayers, as it is for the c variant (perpendicular). 13 On MgO(110), however, Laenens et al found a way to prepare FePt films with the structure rotated about one of the a-axes by 45 • .…”
Section: Methodsmentioning
confidence: 99%
“…Тому актуальним завданням сучасного фізичного матеріялознавс-тва є зниження температури фазового перетворення типу A1-FePt   L1 0 -FePt в нанорозмірних плівкових композиціях на основі FePt [17,18].…”
Section: вступunclassified
“…Припускається, що введення в плівкові композиції на основі проміжних шарів FePt леґувальних елементів (Ag, Cu) може сприя-ти зменшенню температури формування впорядкованої фази L1 0 -FePt через виникнення додаткових напружень внаслідок незбігу параметрів кристалічних ґратниць і температурних коефіцієнтів лінійного розширення шарів [18][19][20][21][22][23][24]. Напруження можуть слугу-вати екстрарушійною силою перебігу дифузійних процесів та про-цесу впорядкування [13,25].…”
Section: вступunclassified